Analysis Of Stock Price At Pt. Telkom Indonesia Tbk Before And After Having Damage On Its Satelit - Setiawan Saleh; Ridwan Tabe (Tasharruf: Journal Economics and Business of Islam, 2018)
This study aims to determine the stock price of PT Telkom Indonesia Tbk before and after damage to the Telkom 1 satellite. In the telecommunications industry, it is very important to know the financial performance in order to achieve the company's goals. The main goal of the company is to maximize the value of the company. High company value can increase prosperity for shareholders, so that shareholders will invest their capital in the company. The value of the company is reflected in the stock price. In Indonesia the government has a telecommunications industry which is a State-Owned Enterprise (BUMN), namely PT. Telkom Indonesia Tbk, as the most complete information and communication company and telecommunication network service and provider in Indonesia. PT. Telkom Indonesia Tbk has a stock price which increases every year from year to year. Towards the end of 2017 PT. Telkom Indonesia Tbk suffered damage to the Telkom 1 satellite, so PT Telkom Indonesia Tbk transferred its network to Telkom 2 satellite. there is a significant difference in the stock price after the damage to the Telkom satellite 1. The stock price before the damage to the Telkom 1 satellite is Rp. 4,730,67 while the share price after the damage to the Telkom 1 satellite was Rp. 4,704.00, which means a stock price decline after the damage to Telkom 1 satellite. Keyword: Analysis, Stock Price.